Fee for Reducing Natural Field Retention as an Instrument of Sustainable Public Finance - Edyta Sygut (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2023)
Theoretical background: Active national fiscal policy is an important determinant of sustainable development. Poland falls below the water security level, which is why natural retention is a particularly important issue, as the poverty of societies begins with a lack of access to water. This also poses a challenge for public finance, which should encourage specific behaviors. As of 1 January 2018, a fee for the reduction of natural land retention is levied in Poland.